P549 Systemic cytomegalovirus infection is a relevant factor affecting short- and long-term outcomes of patients with acute severe ulcerative colitis: An 11-year experience. (16th January 2018) - Macaluso, F S; Compagnoni, S; Renna, S; Maisano, S; Casà, A; Solina, G; Rizzo, A G; La Seta, F; Ventimiglia, M; Orlando, A; Cottone, M
Abstract: Background: Acute severe ulcerative colitis (ASUC) remains a life-threatening condition. Short- and long-term clinical outcomes are still highly variable despite the widespread use of Oxford protocol and the current availability of infliximab (IFX) or cyclosporine (CyA) as rescue therapies. We aimed to report our single-centre experience on clinical outcomes of patients with ASUC and the factors affecting its course. Methods: We retrospectively collected data from 202 consecutive hospital admissions (106 patients) for ASUC from January 2006 to July 2017. The response to intravenous steroids and rescue therapy, and the occurrence of toxic megacolon (TM) were assessed as short-term outcomes, whereas long-term outcomes included remission after 1 year from the episode of ASUC and colectomy free-survival along the entire follow-up. Results: The overall response rates to intravenous steroids and rescue therapy were 47.5% and 91.8% (IFX: 74 of 79, 93.7%; CyA: 16 of 19, 78.9%), respectively, while TM occurred in 24 cases (11.9%). After 1 year from the episode of ASUC, only 25.4% of patients were in continuous clinical remission. After a median follow-up of 37 months (IQR 9.25–98 months), 28 patients (26.4%) underwent colectomy. Colectomy-free survival rates at 3 months and 1 year were, respectively, 82.1% and 77.4%. At multiple mixed-effect regression analysis, systemic CMV infection (defined by blood positivity for CMV-DNA or pp65 antigenemia) was an independent predictor of non-response to IFX rescue therapy (OR 0.12, CI 0.02–0.78, p = 0.031), occurrence of TM (OR 4.21, CI 1.35–13.12, p = 0.013), and colectomy (OR 4.56, CI 1.41–14.55, p = 0.010), together with TM (OR 4.77, CI 1.70–13.35, p = 0.003). Semi-parametric survival Cox analysis confirmed systemic CMV infection (HR 3.54, CI 1.47–8.51, p = 0.005) and TM (HR 3.00, CI 1.35–6.65, p = 0.007) as independent risk factors for colectomy. Conclusions: Detection of CMV in blood–but not on rectal biopsies–is an independent risk factor affecting the main clinical outcomes of patients with ASUC.